Sickle Cell Disease Measures in the Phenx Toolkit - Hassell, Kathryn L.; Eckman, James R.; Klings, Elizabeth S; Adams, Robert J.; Panepinto, Julie A.; Grant, Tracey; Huggins, Wayne; Maiese, Deborah R.; Werner, Ellen M.; Ramos, Erin M.; Hamilton, Carol M. (Blood, 2015)
Background: Common measures and common data elements (CDEs) for sickle cell disease (SCD) are needed to help improve data quality and data comparability necessary for meta-analyses, guidelines development, and implementation science. In recent years, the National Heart, Lung, and Blood Institute (NHLBI) has undertaken several activities to develop CDEs and measures for SCD. These include developing 1) the Sickle Cell Quality of Life Measurement Information System (ASCQ-Me); 2) clinical practice recommendations for the management of SCD; and 3) a lexicon and consensus definitions for the most frequently occurring complications of SCD. In 2014, the NHLBI funded an Administrative Supplement to the PhenX Toolkit to identify common measures to further promote data comparability across SCD research. The Web-based PhenX Toolkit (consensus measures for Phen otypes and eX posures, https://www.phenxtoolkit.org/) provides a catalog of 449 standard measures and associated interoperability resources to help investigators improve quality of data collection and identify opportunities for collaborative research. The development and maintenance of PhenX Toolkit content is driven by the scientific research community. A Steering Committee, comprised of 11 scientists with a wide range of expertise, provides overarching guidance for the project and Working Groups (WG) of subject matter experts select measures for inclusion the PhenX Toolkit. Methods: An 11 member Sickle Cell Disease Research and Scientific Panel (SRSP) was assembled to provide guidance to the project, establish a Core Collection of SCD-related measures, and to define the scope of two Specialty Collections: 1) Cardiovascular, Pulmonary, and Renal Complications and 2) Neuroglogy, Quality of Life, and Health Services. For each Specialty Collection, a Working Group (WG) of seven SCD experts was convened to select high priority measures for inclusion in the Toolkit. Each WG selected representative measures available in the published literature or already in the Toolkit using a consensus process which included input from the scientific community. For each measure, the Toolkit provides a description of the measure, the rationale for its inclusion, detailed protocol(s), and supporting documentation. The Toolkit also provides data collection worksheets and data dictionaries to help integrate PhenX measures into their study design. To support investigators who want to collect data via the Web, PhenX protocols are available as REDCap Instrument Zip files. Results: The Sickle Cell Disease Core and Specialty Collections were released into the Toolkit in August of 2015. The Core Collection, which includes 25 measures covering demographics, socioeconomic status, anthropometrics, pulse oximetry, hemoglobin characterization, history of transfusion, and SCD-related pain episodes, is recommended for use by all NHLBI-funded investigators performing human subjects SCD research. The Specialty Collections are recommended for use within more specialized research areas. The Cardiovascular, Pulmonary, and Renal Specialty Collection includes 11 measures that address heart disease, lung function, and biomarkers for hemolysis, anemia, and iron overload. The Neurology, Quality of Life, and Health Services Specialty Collection includes 8 measures that address developmental delays, stroke risk factors and outcomes, quality of life, and quality of care. A list of other potentially relevant measures from the Toolkit was also developed and annotated for SCD. These measures, including the process, criteria, and rationale for their selection, will be presented. We now have consensus phenotypes of complications in SCD that are available for use in future clinical and epidemiologic studies and for use in harmonizing data across previous studies Implications: For researchers, adoption and use of PhenX standard measures will promote collaborations with clinicians and patients, facilitate cross-study analysis domestically and internationally, accelerate translational research, and lead to greater understanding of phenotypes and epigenetics in SCD. For clinicians, using PhenX measures will help improve patient care and quality of life. Consistent use of these standard measures will establish a common currency to help better understand the etiology, progression, and treatment of SCD. Funding provided by U01 HG004597 and U41 HG007050. Klings:Pfizer: Consultancy; Actelion Pharmaceuticals: Research Funding. Panepinto:HRSA, NIH: Research Funding; NKT Therapeutics, Inc: Consultancy.